Viability and gastrointestinal tolerance of commercial probiotic products - Mohd Akmal, Azhar; Mimi Sakinah, Abdul Munaim; Muzamir, Hasan; Zularisam, Abdul Wahid (International Journal of Pharma Medicine and Biological Sciences, 2020)
The basic principle for probiotic microorganisms to be beneficial to the host is that they must show enough viability when arriving at the intestine as the site of action. Thus, they must be able to stay alive in the lower pH environment in the gastrointestinal tract. The extremely low pH in the human stomach and pepsin enzyme as antimicrobial agents provide an effective barrier toward foreign microorganisms in the human gastrointestinal system. Therefore, the primary purpose of this work is to evaluate the initial viability of the commercial probiotic product and the transit tolerance of the probiotic samples toward low pH in the human gastrointestinal system. In the present study, ten commercial probiotic products available in Malaysia with different types of dosage form were chosen for viability tests and in vitro tolerance toward the human gastric acid environment. The acid tolerance test was conducted at pH 2 for 3 h incubation at 37 °C. The viability was evaluated using a flow cytometer method to determine the cell count. Six out of ten products showed similar or higher viable organism count than the stated label. However, all of the products still met the minimum initial viability requirement for commercial probiotic products, which is 106 CFU per g or mL sample. Generally, all the probiotic product strains cannot tolerate the lower gastric pH environment except for those obtaining enteric coating protection or possessing acidic tolerance.